Padlock and Proximity Probes for in Situ and Array-Based Analyses: Tools for the Post-Genomic Era. Issue 5 (2003) - Landegren, Ulf; Dahl, Fredrik; Nilsson, Mats; Fredriksson, Simon; Banér, Johan; Gullberg, Mats; Jarvius, Jonas; Gustafsdottir, Sigrun; Söderberg, Ola; Ericsson, Olle; Stenberg, Johan; Schallmeiner, Edith
Abstract : Highly specific high-throughput assays will be required to take full advantage of the accumulating information about the macromolecular composition of cells and tissues, in order to characterize biological systems in health and disease. We discuss the general problem of detection specificity and present the approach our group has taken, involving the reformatting of analogue biological information to digital reporter segments of genetic information via a series of DNA ligation assays. The assays enable extensive, coordinated analyses of the numbers and locations of genes, transcripts and protein.